Private Military Force as Strategy to Counter a Hybrid Threat Posture: A Conceptual Framework - Leach, Jonathan (Scientia militaria : South African journal of military studies, 2025)
The international community is currently facing a diffuse, shifting, and controversial set of security challenges. On the one hand, hybrid warfare creates both conceptual and strategic challenges to a state, as conventional military forces are simply not designed to operate in a legal “grey zone”. As a result, certain ways and means, which are essential for the successful prosecution of an armed conflict, must be forfeited. On the other hand, there are significant self-restricting political and legal partitions inherent in the modern strategic landscape, as the international community does not want an easy recourse to war. By having to remain below these political and legal thresholds, a disconnect is however created between the policy ends of a state and the strategic effect of its armed forces. The combined effect of these challenges suggests that there is no suitable policy for dealing with hybrid threats, making the international community particularly vulnerable to exploitation. What is clear is that a more sophisticated, complex, and politically charged strategic response is required to counter a hybrid threat posture - one that effectively links policy ends to the ways and means of achieving those ends. Throughout history many different entities - besides statutory militaries - have fought wars: families, ethnic groups, business enterprises, and private military forces. Today, by virtue of the extensive expertise embedded within the private military industry, private military forces strategically influence both the process and the outcome of conflicts. The objective of the subsequent researchi was therefore to suggest a conceptual framework for private military force to counter a hybrid threat posture. The collective findings of this follow-up research suggest that, if private military force is theoretically coherent; is underpinned by a realistic political dimension; is tailored to a creative and non-linear concept of operations; and is adequately equipped and supported by a state, then the concept of private military force as strategy to counter a hybrid threat posture is a compelling notion.